The effects of cognitive load on pupil dilation in volleyball players: an eye-tracking study - Nalcacigil, T.; Güler, G.; Bidil, S.; Küçük, N.; Toktay, T.; Simsek, D. (European Journal of Human Movement, 2025)
Volleyball is a sport that demands not only high levels of physical exertion but also significant cognitive engagement. Rapid decision-making, attentional control, and visuomotor coordination are essential for optimal performance. This study investigates the effects of cognitive load on pupil dilation and reaction time in competitive volleyball athletes. A within-subjects, controlled experimental design was employed, involving 26 female volleyball players (age 15.4 ± 1.2 years) who regularly train and compete at the regional level. Participants completed three cognitive load conditions in a randomized order: (P1) a motor task requiring the suppression of randomly illuminated lights as quickly as possible, (P2) a cue-based task in which the next light always appeared in the same color zone as the previous one, allowing for anticipatory responses, and (P3) a mixed cue task that introduced a more mixed cue structure, increasing task difficulty and necessitating greater motor control adaptation. Performance was assessed using the Fitlight system, which involved deactivating 25 lights under three distinct levels of cognitive load. To ensure the precise evaluation of cognitive load effects, pupil dilation was continuously measured using Tobii Pro Glasses 2. Results demonstrated that pupil dilation increased significantly under higher cognitive load conditions (p < .001) and that reaction times were faster when predictive cues were available (p < .001). These findings suggest that cognitive load plays a critical role in shaping athletes` visual and motor responses, with direct implications for sports training and decision-making processes. Enhancing cognitive training protocols in volleyball may improve athletes` ability to process visual information efficiently and execute rapid motor responses under high-pressure conditions.